Transcriptional signatures of invasiveness in Meloidogyne incognita populations from sub-Saharan Africa - Cox, D.; Reilly, B.; Warnock, N.D.; Dyer, S.; Sturrock, M.; Cortada, L.; Coyne, D.; Maule, A.G.; Dalzell, J.J. (Elsevier, 2019)
Meloidogyne incognita is an economically important plant parasitic nematode. Here we demonstrate substantial variation in the invasiveness of four M. incognita populations relative to tomato. Infective (J2) stage transcriptomes reveal significant variation in the expression of protein-coding and non-coding RNAs between populations. We identify 33 gene expression markers that correlate with invasiveness, and which map to genes with predicted roles in host finding and invasion, including neuropeptides, ion channels, G Protein-Coupled Receptors, cell wall-degrading enzymes and microRNAs. These data demonstrate a surprising diversity in microRNA complements between populations, and identify gene expression markers for invasiveness of M. incognita, to our knowledge for the first time.